Pengelolaan Sampah Plastik Daerah Kepulauan di Siberut Selatan Mentawai - Nofi Yendri Sudiar; Asrizal Asrizal; Pakhrur Razi; Mohammad Isa Gautama (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
Day to day, the volume of plastic waste in Indonesia is increasing along with the increasing number of products and people's consumption patterns. According to data in 2021, the total national waste was 68.5 million tons. The main thing that must be done to overcome the case is to reduce the volume of plastic waste from its source through community empowerment about the importance of caring for environmental cleanliness. Problems regarding the management of plastic waste in the islands of South Siberut, among others, most (83.3%) of the community still do not separate organic and inorganic waste. Second, most (61.1%) of the community have not separated plastic waste. Furthermore, most people (83.3%) have never made compost from household waste. Finally, most (77.8%) of the people shopping at the market have not brought their own shopping bags. This community service activity is carried out through lecture presentation methods, discussions and workshops. This activity aims to increase public awareness about the dangers of plastic waste, and transform people's behavior to be able to manage the flow of plastic waste independently. From the results of the community service program that has been carried out, there has been an increase in public interest in the context of changing behavior in managing plastic waste.